Penentuan Aftershock Gempabumi Yogyakarta Tanggal 6 Juni 2006 Dengan Menggunakan Metode Geiger - Dinda Shakila Farah; Setyoajie Prayoedhie; Budiarta Budiarta; Dini Vermiratih; Yusuf Hadi Perdana (Stasiun Geofisika Kelas I Sleman, 2023)
The 2006 Yogyakarta earthquake was a shallow crustal tectonic earthquake that rocked the Special Region of Yogyakarta (DIY) and its surroundings on May 27, 2006. This earthquake was followed by many aftershocks up to 10 days later, namely on June 6, 2006. To get information about the distribution aftershock of earthquake, aftershock parameter processing was carried out on June 6, 2006. Determination of the aftershock parameters was carried out using SeisComp3 software with the principles and theory of the Geiger method. The Geiger method is a method that uses least squares optimization to determine the hypocenter and epicenter points. There were 122 earthquakes that occurred on June 6, 2006 with earthquake magnitudes ranging from 0.8 – 3.7 and occurring at depths of 1.5 km – 18.6 km. Aftershock aftershocks spread along the border of Bantul and Gunungkidul Regencies, due to the Opak fault and the many minor faults around the Opak fault. This causes the Bantul and Gunungkidul Regency areas to be very active in terms of seismicity.